Ten years on, the "Three Circle" model of restorative & transformative justice: A tool to combat victimization and recidivism - Goulding, Dot; Steels, Brian (Springer, 2013)
This paper had its genesis 10 years ago in the authors’ development of a communitarian ‘three circle’ model of restorative and transformative justice for a pilot restorative justice study used with serious and repeat adult offenders appearing in the Magistrates’ Courts in Western Australia. The model was designed in part to place their crimes within a context, something that rarely occurs within the mainstream adversarial criminal justice system in Australia. The model was primarily designed to provide victims of crime with the best outcome and offenders with the opportunity to provide apology and restitution, as well as take responsibility for their actions. The three circles, each including two facilitators, are: Circle 1: consists of the perpetrator who has pleaded guilty to a specified criminal act together with his/her family and/or friends; Circle 2: consists of the victim(s) of the crime together with their family and/or friends. Circle 3: consists of a combination of the first two circles, tasked to seek, if possible, a mutually agreeable resolution that culminates in a report to present to the Magistrate in court to use in mitigation of sentencing. Importantly, although the 30-month study had socially and economically significant results, 10 years after its completion there is still no restorative justice program in the adult courts in Western Australia. Because of this, the authors also set out to question the state government’s motivation in largely ignoring this successful process.